The Impact of Using the Internet of Things in Improving the Quality of Teachers' Communication and The Quality Of Education In Indonesia - Rieneke Ryke Kalalo; Taransa Agasya Tutupoly; Dewi Anggreini; Gede Erik Aktama; Apriani Riyanti (Yayasan Inovasi Kemajuan Intelektual, 2025)
The rapid evolution of digital technology in 2026 has positioned the Internet of Things (IoT) as a cornerstone of educational reform globally, particularly in the Indonesian context. This research investigates the strategic impact of IoT integration on two critical dimensions: teacher communication quality and overall education quality. Utilizing a quantitative approach with a sample of 500 educators across various provinces in Indonesia, this study examines how IoT-enabled devices—such as smart whiteboards, wearable technology, and automated attendance systems—facilitate real-time data exchange and interpersonal engagement. The conceptual framework is grounded in the Unified Theory of Acceptance and Use of Technology (UTAUT). Preliminary findings suggest that IoT significantly enhances communication quality by providing teachers with synchronized platforms for student-parent interaction, thereby reducing information asymmetry. Furthermore, the automation of administrative tasks through IoT enables educators to devote more time to pedagogical innovation, which directly correlates with improved educational outcomes. However, the study also identifies persistent challenges, including the digital infrastructure gap between urban and rural regions in Indonesia. This research concludes that while IoT serves as a powerful catalyst for educational excellence, its success depends on equitable access to technology and comprehensive teacher training programs.